Hubungan Gerakan Literasi Sekolah dalam Meningkatkan Minat Membaca Peserta Didik SD Negeri 4 Metro Timur - Prayoga, M. Iqbal; Siska Mega Diana; Roy Kembar Habibie; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' reading interest at SD Negeri 4 Metro Timur still shows low scores and is one of the important problems in learning. One program developed to address this problem is the School Literacy Movement. This study aims to analyze the relationship between the School Literacy Movement and increased reading interest in second-grade students at SD Negeri 4 Metro Timur. This study used a quantitative approach with an ex post facto design. The research subjects were 88 students. Data collection was carried out through questionnaires and documentation, while data analysis used simple linear regression. The results showed that the relationship between the school literacy movement and increased student reading interest contributed 16.1%. This finding suggests that the implementation of a planned and sustainable school literacy movement can increase reading interest in elementary school students.